Answers

2014-12-08T12:23:22+05:30
1)   15x² - 26x + 8
⇒ 15x² - 20x - 6x + 8
⇒ 5x(3x - 4) - 2 (3x - 4)
⇒ (3x - 4)(5x - 2)

2) p² + 16p - 16
There is an error in this.
It can be solved if it changed to p² + 15p - 16

⇒ p² + 16p - p - 16
⇒ p(p+16) - 1(p+16)
⇒ (p+16)(p-1) 

3) 3x² - 4x - 4
⇒ 3x² - 6x + 2x - 4
⇒ 3x(x-2) + 2(x - 2)
⇒ (x - 2)(3x + 2)

4) x² - 5/12 x + 1/24
⇒x² - x/6 - x/4 + 1/24
⇒ x(x - 1/6) - 1/4(x - 1/6)
⇒ (x - 1/6)(x - 1/4)

0
2014-12-08T17:14:09+05:30
1.15x² - 26x + 8
 15x² - 20x - 6x + 8
 5x(3x - 4) - 2 (3x - 4)
(5x - 2) (3x - 4)


2. p² + 15p - 16
 p² + 16p - p - 16
 p(p+16) - 1(p+16)
 (p+16)(p-1) 

3. 3x² - 4x - 4
 3x² - 6x + 2x - 4
 3x(x-2) + 2(x - 2)
 (x - 2)(3x + 2)

4. x² - 5/12 x + 1/24
x² - x/6 - x/4 + 1/24
 x(x - 1/6) - 1/4(x - 1/6)
 (x - 1/6)(x - 1/4)
0